The challenge of imagining integral citizenships - Yangali Vargas, Jorge Luis (2020)
On the eve of the bicentennial, the National Education Council of Peru published the National Education Project (2020) (or PEN 2036); a long-range proposal, like its predecessor, the PEN of 2006, since its horizon is 2036 and its main goal is the formation of full citizens. Due to the context, structural corruption and institutional precariousness that each new generation inherits from the other (García, 2016; Quiroz, 2013), the governing class - understood as the officials of the Ministry of Education and the members of the National Education Council (CNE) - proposes to Peruvian society in general, and educators in particular, to make a joint effort to achieve full citizenship.